Investigating effects of the excessive growth of aquatic plants on water quality in Anzali Lagoon, south-western Caspian Sea - Y. Filizadeh; H. Khodaparast (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2004)
In this study, excessive growth in submerged aquatic plants such as Coontail (Ceratophyllum demersum) and Pondweed (Potamogeton spp.), floating-leaved species such as Lotus (Nelumbo nucifera) and free-floating species such as Water Fern (Azolla filiculoides) in Anzali Lagoon was observed. We studied effects of excessive growth of these plants on water quality in Anzali Lagoon over the years 1998-2000. Assessed the possible effects of canopy formation and growing sites of these plants on habitat of aquatic animals was studied too. We showed that dissolved oxygen concentration (DO), pH and water temperature are associated with the growth and distribution of the aquatic plants, and established a significant relationship between vertical DO, pH and water temperature and location of canopy of these plants in the water column. Also, an increase in the amount of DO and pH in areas around the canopy and under it for submerged plants observed. This was not the case for floating-leaved and free-floating aquatic plants. The higher water turbulence in areas free from aquatic plants increased DO in lower layers of water column compared to areas covered with aquatic plants. We related the amount of DO and pH of water to growth form in aquatic plants that determines location of canopy formation in these plants. Contrary to the location of canopy and growing site factors, the extent of growth of these plants did not show an effect on DO and pH of water.